Molecular Signature of Prospero Homeobox 1 (PROX1) in Follicular Thyroid Carcinoma Cells - Rudzińska, Magdalena (Int J Mol Sci, 2019)
The prospero homeobox 1 (PROX1) transcription factor is a product of one of the lymphangiogenesis master genes. It has also been suggested to play a role in carcinogenesis, although its precise role in tumour development and metastasis remains unclear. The aim of this study was to gain more knowledge on the PROX1 function in thyroid tumorigenesis. Follicular thyroid cancer-derived cells—CGTH-W-1—were transfected with PROX1-siRNA (small interfering RNA) and their proliferation, cell cycle, apoptosis and motility were then analysed. The transcriptional signature of PROX1 depletion was determined using RNA-Sequencing (RNA-Seq) and the expression of relevant genes was further validated using reverse transcriptase quantitative PCR (RT-qPCR), Western blot and immunocytochemistry. PROX1 depletion resulted in a decreased cell motility, with both migratory and invasive potential being significantly reduced. The cell morphology was also affected, while the other studied cancer-related cell characteristics were not significantly altered. RNA-seq analysis revealed significant changes in the expression of transcripts encoding genes involved in both motility and cytoskeleton organization. Our transcriptional analysis of PROX1-depleted follicular thyroid carcinoma cells followed by functional and phenotypical analyses provide, for the first time, evidence that PROX1 plays an important role in the metastasis of thyroid cancer cells by regulating genes involved in focal adhesion and cytoskeleton organization in tumour cells.